Functional Expression Study of Igf2 Antisense Transcript in Mouse. (28th December 2013) - Duart-Garcia, Carolina; Braunschweig, Martin H.
Abstract : Insulin-like growth factor antisense gene ( Igf2as ) expression was investigated in different mouse tissues during development, in differentiating C2C12 cells and in a Δ DMR1-U2 knockout mouse model. The expression levels of Igf2as were high in fetal and newborn liver and muscle tissues compared to adults. The Igf2as gene was also expressed in placenta and in brain. The expression data suggests that the Igf2as gene plays a role in early development of the mouse and in placenta. There was no consistent evidence for an interaction between Igf2 and Igf2as transcripts. Furthermore, in knockout placentas lacking Igf2as transcription, Igf2 expression was comparable to that in wild type. These results indicate that Igf2as does not regulate Igf2 sense transcripts. In previous studies, it was suggested that the Δ DMR1-U2 knockout mouse showing intrauterine growth restriction was caused by the absence of placenta-specific Igf2 P0 transcription. We conclude that the Δ DMR1-U2 deletion phenotype should be reconsidered in the light of a functional Igf2as gene.